2011
DOI: 10.1371/journal.pone.0019165
|View full text |Cite
|
Sign up to set email alerts
|

The Music of Your Emotions: Neural Substrates Involved in Detection of Emotional Correspondence between Auditory and Visual Music Actions

Abstract: In humans, emotions from music serve important communicative roles. Despite a growing interest in the neural basis of music perception, action and emotion, the majority of previous studies in this area have focused on the auditory aspects of music performances. Here we investigate how the brain processes the emotions elicited by audiovisual music performances. We used event-related functional magnetic resonance imaging, and in Experiment 1 we defined the areas responding to audiovisual (musician's movements wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…This suggests that its role during the aesthetic experience of dance may be related with the observer's motor simulation response. Activity in the inferior parietal gyrus and the occipitotemporal cortex (EBA) has also been associated with the processing of emotional body movements, such as emotional point light displays of emotions, emotional gestures, or the emotional movements of a musician (without music) Peelen, Atkinson, Andersson, & Vuilleumier, 2007;Petrini, et al, 2011). Surprisingly, however, activity in classical emotion-processing regions, such as the insula, the orbitofrontal cortex, and the anterior cingulate cortex (Adolphs, 2002;Keysers, Kaas, & Gazzola, 2010;Petrini, et al, 2011), has so far been reported only for tasks of dance observation (Cross, Kirsch, Ticini, & Schuetz-Bosbach, 2011;Jang & Pollick, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that its role during the aesthetic experience of dance may be related with the observer's motor simulation response. Activity in the inferior parietal gyrus and the occipitotemporal cortex (EBA) has also been associated with the processing of emotional body movements, such as emotional point light displays of emotions, emotional gestures, or the emotional movements of a musician (without music) Peelen, Atkinson, Andersson, & Vuilleumier, 2007;Petrini, et al, 2011). Surprisingly, however, activity in classical emotion-processing regions, such as the insula, the orbitofrontal cortex, and the anterior cingulate cortex (Adolphs, 2002;Keysers, Kaas, & Gazzola, 2010;Petrini, et al, 2011), has so far been reported only for tasks of dance observation (Cross, Kirsch, Ticini, & Schuetz-Bosbach, 2011;Jang & Pollick, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Activity in the inferior parietal gyrus and the occipitotemporal cortex (EBA) has also been associated with the processing of emotional body movements, such as emotional point light displays of emotions, emotional gestures, or the emotional movements of a musician (without music) Peelen, Atkinson, Andersson, & Vuilleumier, 2007;Petrini, et al, 2011). Surprisingly, however, activity in classical emotion-processing regions, such as the insula, the orbitofrontal cortex, and the anterior cingulate cortex (Adolphs, 2002;Keysers, Kaas, & Gazzola, 2010;Petrini, et al, 2011), has so far been reported only for tasks of dance observation (Cross, Kirsch, Ticini, & Schuetz-Bosbach, 2011;Jang & Pollick, 2011). Activity in such regions has not been found to be especially relevant in tasks of aesthetic appreciation of dance movements, which may be puzzling considering the rather large amount of empirical and theoretical work linking emotional and affective processes with art appreciation (Leder, Belke, Oeberst, & Augustin, 2004;Aharon, Etcoff, Ariely, Chabris, O'Connor, Breiter, 2001;Blood & Zatorre, 2001;Brown, Martinez, & Parsons, 2004;Vartanian & Goel, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, early interactions of body and vocal expressions are reliably observed [6], [7], and an interaction has also been reported between body motion and music produced by the very body motion [8], [9]. However, do these interactions truly reflect integration [10]?…”
Section: Introductionmentioning
confidence: 99%
“…Characterized by superior temporal resolutions of expressive qualities, sonic dimensions, like music, are highly suitable to take over other senses during the initial direction of selective attention towards congruent perceptions [43] [26]. Thus, situation-specific associative and expectation driven evaluative functions of music influence the scenic interpretation in accordance to audio-visual correspondence as well as visual perception [6] [10] [33]. When expressive qualities of music stimuli become salient, multisensory expectations on emotional congruency towards the environment, termed hypotheses of perception, are formed.…”
Section: Music and Immersionmentioning
confidence: 99%